Avaliação dos limites e restrições do fundo estadual de combate à pobreza do estado do Ceará – FECOP, um caso particular - Cavalcante, Valberg Barbosa (2013)
The design of the proposed study to be described is a theme related to the Fund to Combat Poverty in the State of Ceará – FECOP, which was established by complementary Law No. 37, dated November 26, 2003 and regulated by State Decree 27379, which seeks to support the actions of public policies in overcoming poverty in the State of Ceará, in two-pronged in the structural change and the processes of compensatory policies, that involve all actions of state departments of Ceará in fighting poverty, and the proposed project seeks to put as problematic if this public policy is really reducing poverty in the State of Ceará, and what is its nature of operations in the period from 2004 to 2010, set against the backdrop Neo-Liberal and globalization of financial capitalism, as constituent elements of the expanded reproduction of poverty so widespread throughout developing countries, within an unfair inclusion of capitalist globalization. The main objective of this study is to evaluate, analyze critically and reflectively the implementation, concepts, principles and achievements of FECOP, regarding the behavior of the indices related to extreme poverty and poverty in the aforementioned period, in a differently and more comprehensive than the dominant explanatory variable used and focused only on insufficient income.